PEMERTAHANAN BAHASA IBU STUDI KASUS BAHASA JAWA DI PAPUA - Supriyanto Widodo (Balai Bahasa Provinsi Papua, 2019)
This study is observation result of writer on Javanese society that lives in Jayapura’s City and Regency of Jayapura, Papua.Defending of Javanese language as mother tongue at Papuan is not despite existence programs resettlement. Transmigran’s society that lives at resettlement region while in daily communication still using Javanese language. Javanese society who are not transmigran and living at urban have not more used Javanese in daily conversation. But, on special chances, e.g. on arisan’s event society, they still to speak javanese. Even so, its javanese has mingled with Indonesian so as they converse frequent happening code switching and code mingling.